The relationship between the organization of work in the private sector and the planning of education " Analytical study and model of the case study of vocational education in the city of Latakia " - غانم, ثناء (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The research aims to define the relationship of regulation work in the private sector to education planning. The research adopted the descriptive methods to achieve this goal, and applied the individual and focus group interview to collect data from the research sample (89 interviews) in Lattakia. The results of the research showed that: the organization of work in the private sector, characterized by the advantages of working in the public sector, will facilitate the building of real databases on the labour market that will help to identify the need for workers in different fields. The extent to which training is needed to develop certain occupations, and identify new occupations that are disappearing, taking into account the development of occupations and the labor market when accepting students and developing appropriate educational and training programmes, making education planning more realistic and more suitable for the labor market. The quality of education improves and the risks of working of the work decrease, which contributes to improve the status of work in the private sector and making it more attractive to job seekers.